Функціональна характеристика нейромоторного апарату нижніх кінцівок у юнаків - Абрамчук, Ольга Миколаївна; Аршулік, Тетяна; Abramchuk, Olha M.; Arshulik, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2013)
Для вивчення функціонального стану нейромоторного апарату нижніх кінцівок було проведено електроміографічне дослідження 30 осіб з різним рівнем рухової активності. Результати наших експериментів вказують на те, що величина сили стимулу під час якої реєструвалась максимальна М-відповідь та Н-рефлекс була вірогідно нижча у юнаків-спортсменів. Встановлено, що у групі спортсменів показники амплітуди М-відповіді та Н-рефлексу були значно вищими порівняно з контролем. Аналіз максимальної латентності М-відповіді та Н-рефлексу у групі спортсменів та контрольній групі показав вірогідні відмінності за показниками Н-рефлексу.

For the study of the functional state of neuromotor vehicle of lower limbs it was conducted electromyographic researches of 30 persons with the different level of motive activity . The group of sportsmen consisted with the students of institute of physical culture and health and and male-youths that constantly visited certain sport sections. The research was conducted by means of multifunction computer complex " Neuro - МВП " applying stimulant EMG methodology. The results of our experiments show that the size of force of stimulus under which maximal M-answer and Н- reflex were registered was remarkably lower for young sportsmen. It is fixed, that in the group of sportsmen indices of amplitude of M-answer and Н - reflex were considerably higher as compared to control . The analysis of maximal latency of M-answer and Н - reflex in the group of sportsmen and control group showed clear cut distinctions regarding the H-reflex indices. The indices of M-answer maximal latency by sportsmen were noticeably lowew as compared to control . It is shown that in the group of sportsmen the correlation of maximal amplitudes M - and Н - answers was higher comparatively with control, however reliable distinctions were not revealed.
Functional state of neuromotor system of lower limbs for male-youths
Keywords: електроміографія; electromyography; М-відповідь; M-answer; Н-рефлекс; Н-reflex